7(t+4)+3(2t-5)=

Simple and best practice solution for 7(t+4)+3(2t-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(t+4)+3(2t-5)= equation:


Simplifying
7(t + 4) + 3(2t + -5) = 0

Reorder the terms:
7(4 + t) + 3(2t + -5) = 0
(4 * 7 + t * 7) + 3(2t + -5) = 0
(28 + 7t) + 3(2t + -5) = 0

Reorder the terms:
28 + 7t + 3(-5 + 2t) = 0
28 + 7t + (-5 * 3 + 2t * 3) = 0
28 + 7t + (-15 + 6t) = 0

Reorder the terms:
28 + -15 + 7t + 6t = 0

Combine like terms: 28 + -15 = 13
13 + 7t + 6t = 0

Combine like terms: 7t + 6t = 13t
13 + 13t = 0

Solving
13 + 13t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 13t = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 13t = 0 + -13
13t = 0 + -13

Combine like terms: 0 + -13 = -13
13t = -13

Divide each side by '13'.
t = -1

Simplifying
t = -1

See similar equations:

| 19-y=x-x | | 7(q+2)=7q+14 | | 2x+4x=21 | | =8+8 | | 2x=62 | | x+2(y-x)=5+x | | 4x+27=191 | | 5r^2-39r-8=0 | | -15=-7y+4(y+3) | | 5(29-5x)=x-112 | | -2u+5=9-3u | | 2x+17=74 | | 3x-24+5x=7x+24 | | 12x+3y=y+9 | | 2(3y+4)=4-3 | | 0.5(4x-10)=x+15 | | 66-5x=31x+18 | | 6x+7.1=20.3 | | 2x+12=380 | | x(5x+30)=0 | | 11-10x=147-38x | | 7x+4=9x+13 | | p^2+16p=-15 | | 8(4d-6)= | | 103-2x=6x+7 | | m^2-10m=39 | | 180X+x+59= | | 3(a+3)= | | 18X+50=140 | | a^2+24a=0 | | 3x-3+3x=37 | | 12x-3y=8 |

Equations solver categories